PENGARUH STRES DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT EPSON BATAM - Dwi Kartikasari; Kintan Benvia Cherny (Politeknik Negeri Batam, 2017)
The purpose of this study is to determine the effect of stress at work and working motivation on the productivity at the PT Epson Batam. This study had used Explanatory research as main method and Area Sampling as sampling method. Sample were taken as a part from the population that is one hundred employees. Data were taken by using list of question. Data were analyzed by using Regression Method and through SPSS 20. The result of the study have shown that stress at work and working motivation significantly influence the employee’s working productivity.